2017
DOI: 10.1016/j.drugalcdep.2017.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Everyday functional ability in HIV and methamphetamine dependence

Abstract: Background Methamphetamine (METH) use is a risk factor for the transmission of HIV. Each is associated with neurocognitive impairment and subsequent problems in everyday functioning, yet additive effects of HIV and METH are not consistently observed. This study used the UCSD Performance-Based Skills Assessment (UPSA-2) to assess whether METH use disorder and HIV together resulted in poorer functional outcome than either condition alone. Method Participants in the Translational Methamphetamine AIDS Research C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…This relationship may be further compounded by increased apathy, which is also independently associated with executive function deficits and learning difficulties ( Castellon et al, 2000 , Cole, 2007 ). Combined with evidence linking NCI with a variety of other adverse health and functional outcomes in METH users, which may further interfere with treatment outcomes ( Aharonovich et al, 2003 , Henry et al, 2010 , Minassian, 2017 , Sadek, 2007 , Weber, 2012 ), individuals should be screened for NCI prior to treatment to appropriately tailor intervention strategies to their cognitive strengths and/or weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship may be further compounded by increased apathy, which is also independently associated with executive function deficits and learning difficulties ( Castellon et al, 2000 , Cole, 2007 ). Combined with evidence linking NCI with a variety of other adverse health and functional outcomes in METH users, which may further interfere with treatment outcomes ( Aharonovich et al, 2003 , Henry et al, 2010 , Minassian, 2017 , Sadek, 2007 , Weber, 2012 ), individuals should be screened for NCI prior to treatment to appropriately tailor intervention strategies to their cognitive strengths and/or weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, clinical studies found that HIV and a history of METH dependence additively impaired cognitive function (Kesby et al, 2015;Rippeth et al, 2004). However, other clinical studies found that HIV and METH dependence did not additively impair everyday functional skills (Minassian et al, 2017) or impulsivity, disinhibition, or sensation-seeking (Marquine et al, 2014). Therefore, combined HIV and METH dependence likely has varying effects on CNS processes depending on the function examined.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive deficits are thought to substantially impact the ability to engage in the vital tasks of daily living. Although comorbid HIV-1 infection and METH dependence have been associated with worsening cognitive performance, additive effects of HIV-1 and METH were not observed for everyday functioning [ 139 ]. Results from two recent human studies demonstrated that individuals with comorbid HIV-1 and METH use disorder exhibited the highest rates of frailty (state of increased vulnerability to multisystem damage) and significantly poorer sleep quality compared to singly affected (HIV-/METH+ and HIV+/METH-) groups [ 140 , 141 ].…”
Section: Combined Effects Of Hiv-1 Infection and Methamphetamine Use On Neurocognitive Functioningmentioning
confidence: 99%